A policontexturalidade da Lex Mercatoria: contingência, paradoxo e decisão - Luz, Cícero Krupp da (Universidade do Vale do Rio do Sinos, 2009)
The lex mercatoria is part of a global legal pluralism which reemerges with globalization and consolidation of world differentiated society. Through the autopoietic social systems theory is carried out a construction of a new meaning to the lex mercatoria. This construction is based on a systemic architecture that requires three key issues: contingency, paradox and decision; the three chapters are divided like that. The first chapter seeks between the historical evolution contingency an identity with the differentiated global society, to rebuild a meaning for the lex mercatoria. Thus, the hypercomplex observation generates an operational polycontexturality. From these two concepts the lex mercatoria may have a new direction and new communicative elements. The second chapter is facing the paradoxes of the lex mercatoria: Law without State is reconstructed by a Heterarchichal Law; droit corporatif by structural couplings; contract sans loi by soft law, customary Law by episodic Law. These four communicative ele
Keywords: arbitragem; comércio transnacional; direitos humanos; policontexturalidade; teoria dos sistemas sociais autopoiéticos; lex mercatoria; arbitration; autopoietic social systems theory; human rights; transnational trade; polycontexturality; Ciências Sociais Aplicadas